(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Nirgundi is a large aromatic shrub or small tree grows upto 4.5m height common throughout the country. Nirgundi is clinically used in many diseases by all most all traditional system of medicine because of its diverse medicinal properties. The drug was mentioned during Vedic period and was used in various diseases in Ayurveda since Samhita kala. Nirgundi is having Katu Tikta Kashaya Rasa, Laghu Ruksha Guna, Ushna Veerya and Vata Kaphahara property. Nirgundi is having Deepani, Kusghtaghna, Krimighna, Medhya, Shothahara, Shulahara Karma, and mainly used in Vatavyadhi, Karna Roga, Krimi Kushta, Rajayakshma, Gulma Chikitsa. For the fulfillment of treatment in Ayurveda the knowledge of Dravya including its Rasapanchaka, synonym are very important, without the knowledge of which the treatment is impossible. Nirgundi is one such drug having diversified properties and the opinion of different authors regarding the use of the drug is very necessary in treating diseases starting from common fever to anxiety. Thus the synonyms and their interpretation, Vernacular names, Rasapanchaka, Rogaghnata and Karma, Yoga of Nirgundi in Brihatrayi and various Nighantus Dhanwantri Nighantu, Shodhala Nighantu, Madanpala Nighantu, Kaiyadeva Nighantu, Raja Nighantu and Bhavprakasha Nighantu, has been described and this paper presented a classical review of Vitex negundo Linn. mentioned in Ayurveda.